2016
DOI: 10.3892/ol.2016.5323
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PDCD4 mediated by the long non-coding RNA HOTAIR inhibits the proliferation and invasion of glioma cells

Abstract: Abstract. Programmed cell death protein 4 (PDCD4) has recently been demonstrated to be implicated in translation and transcription, and the regulation of cell growth. However, the mechanisms underlying PDCD4 function in glioma cells remain to be elucidated. The current study investigated the function and regulation of PDCD4 and the results demonstrated that the expression of PDCD4 was significantly reduced in glioma cells compared with normal cells. When PDCD4 was overexpressed in glioma cells, the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Downregulation of HOTAIR can inhibit the proliferation, invasion and migration of tumor cells, and meanwhile promote the apoptosis of glioma cells. 2,19 In our study, the relative expression of HOTAIR was lower in glioma tissues of grade I than in the case of grades II-IV, and multivariate analysis showed that high expression of HOTAIR (>0.40) was an independent risk factor for grades II-IV. These results suggested that HOTAIR was associated with the grades of gliomas and could act as a biomarker reflecting the invasiveness of gliomas.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Downregulation of HOTAIR can inhibit the proliferation, invasion and migration of tumor cells, and meanwhile promote the apoptosis of glioma cells. 2,19 In our study, the relative expression of HOTAIR was lower in glioma tissues of grade I than in the case of grades II-IV, and multivariate analysis showed that high expression of HOTAIR (>0.40) was an independent risk factor for grades II-IV. These results suggested that HOTAIR was associated with the grades of gliomas and could act as a biomarker reflecting the invasiveness of gliomas.…”
Section: Discussionsupporting
confidence: 44%
“…As the most common primary tumors in the central nervous system among adults, 1,2 gliomas are classified into 4 grades that reflect the degree of invasiveness/malignancy according to the current 2016 World Health Organization (WHO) Classification of Tumours of the Central Nervous System. 3 Grade I refers to benign and more circumscribed tumors with low proliferative potential.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs can exhibit oncogenic or tumour suppressive functions [ 11 ]. Regarding processes of tumour growth, all three were found to be involved in cell proliferation in glioma [ 39 , 53 55 ] and various other cancer types [ 56 61 ]. As an oncogenic lncRNA, HOTAIR is involved in epigenetic gene silencing, cell growth, and progression of various cancers [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CASC15 was previously revealed to be involved in the tumorigenesis of gastric cancer via interacting with EZH2 and WDR5 in nucleus [ 15 ]. PDCD4, a tumor suppressor, was previously proved to be down-regulated by PRC2 complex via increasing the level of H3K27me3 at its promoter in glioma [ 18 ]. Thus, we wondered whether CASC15 could regulate PDCD expression through EZH2 in melanoma.…”
Section: Resultsmentioning
confidence: 99%